Pengembangan LKPD IPAS Berbasis Problem Based Learning pada Materi Siklus Hidup Makhluk Hidup Kelas III SDN Campor 2 Geger Bangkalan - Fadilatul Fitriyah; Isna Ida Mardiyana (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The background of this study was the limited availability of teaching materials used in the learning process, which hindered students' understanding of the subject matter. As a result, students learning outcomes in Science and Social Studies (IPAS), particularly on the topic of life cycles, remained low. This study aimed to develop an Integrated Science and Social Studies Student Worksheet (LKPD IPAS) based on the Problem-Based Learning model for the animal life cycle material for third-grade students at UPTD SDN Campor 2, Geger District, Bangkalan Regency. This study employed a Research and Development (R&D) method using the 4D model: Define, Design, Develop, and Disseminate. Data were collected through interviews, observations, questionnaires, and tests. The results showed that the developed LKPD met the criteria of validity, effectiveness, and attractiveness. Product validity was demonstrated by expert validation scores from learning design experts (96.66%), material experts (96.42%), and teaching material experts (95.31%), all categorized as highly valid. Product effectiveness was indicated by 90% classical learning mastery and supported by student activity observations (90.83%), categorized as highly effective. Product attractiveness was shown by student responses (91.83%), this value is categorized as highly attractive. Therefore, the developed LKPD is suitable for use in the learning process.